2018
DOI: 10.1159/000497297
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Ameliorate the Pancreatic Changes of Chemically Induced Hypothyroidism by Carbimazole in Male Rats

Abstract: We induced hypothyroidism (HT) in male rats through chronic oral administration of carbimazole and then tested whether an i.v. injection of rat bone marrow-derived mesenchymal stem cells (BM-MSCs) could ameliorate the HT-induced changes in pancreatic structure and function. The thyroid and pancreatic function tests, as well as total antioxidant capacity (TAC) and malondialdehyde (MDA) were estimated. The pancreatic structure was evaluated by hematoxylin and eosin (H&E) stain. Insulin protein and cleaved caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Moreover, extensive vacuolation was clearly evident within the acinar and ductal cytoplasm of group II. This comes in agreement with previous study which reported shrinkage in the acini and cytoplasmic vacuolation in pancreatic tissue of hypothyroid rats (16) .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, extensive vacuolation was clearly evident within the acinar and ductal cytoplasm of group II. This comes in agreement with previous study which reported shrinkage in the acini and cytoplasmic vacuolation in pancreatic tissue of hypothyroid rats (16) .…”
Section: Discussionsupporting
confidence: 94%
“…H and E-stained slices of the pancreas of control rats revealed the following findings in the current study: normal architecture this was in agreement with Arafa et al (21) who described that it was formed of serous acini in which the cells were pyramidal in shape with round nuclei at the base of the cell. The cytoplasm appeared basal basophilic and apical acidophilic.…”
Section: Discussionsupporting
confidence: 92%
“…It was mentioned that thyroid hormones have a well-known effect in the maturation of fungiform papilla. Thus, hypothyroidism could act as a damaging factor for the development of the papillae with subsequent decrease in taste perception (25) .…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in BM-MSC treated group might be explained by several potential mechanisms. First; indirectly as systemic injection of BM-MSCs may cause regeneration of the thyroid gland (25) . Secondly; directly by homing of injected BM-MSCs in the tongue papillae and trans-differentiation into a diversity of cell types needed for tissue regeneration (14) , this explanation was supported here by the fluorescent PKH26 labeled cells detection within the tissues of the tongue.…”
Section: Discussionmentioning
confidence: 99%